Development of the multifunctional rescue robot FUHGA2 and evaluation at the world robot summit 2018. (17th January 2020) - Takemori, Tatsuya; Miyake, Masato; Hirai, Tomoaki; Wang, Xixun; Fukao, Yuto; Adachi, Mau; Yamaguchi, Kaiyo; Tanishige, Suomi; Nomura, Yusuke; Matsuno, Fumitoshi; Fujimoto, Toshiaki; Nomura, Akito; et al.
Abstract: Robots are needed in rescue activities and the inspection of infrastructure. We developed the rescue robot FUHGA2 so that it has various functions. FUHGA2 has high mobility, with main crawlers covering the body and four sub-crawlers, high dexterity using a long six-axis arm, and high searching ability using various sensors. Furthermore, a novel parallel gripper unit with wire-jamming mechanism is mounted at the tip of the arm, which can change its hardness and fit its shape to an object. Additionally, high Maneuvering is achieved by displaying sensor information to the operator clearly and intuitive operation command design. FUHGA2 won the World Robot Summit 2018 Standard Disaster Robotics Challenge, which is a competition for rescue robots. We achieved high scores in all categories of tasks. In this paper, we describe the development of FUHGA2 and the performance evaluation results from the World Robot Summit 2018. GRAPHICAL ABSTRACT: